Assessment of Two Female Broiler Rearing Systems (Traditional and Modern) and Their Repercussion on Wellbeing, Corticosterone Concentration, Lesions in Adrenal Glands and Productive Parameters - Servin , R. Jorge; Quintana, L. Jose; Casaubon, H. Marie; Gonzalez, A. Mariano; Rojas, M. Susana (International Journal of Poultry Science, 2013)
The effect of two rearing systems on productive performance and level of wellbeing in broilers reared up to day 46 was assessed. The birds were subjected to two treatments: (T1) traditional rearing (open drinkers, population density of 10.7 birds/m2 and infrared light bulbs as heating source), with 4 repetitions of 6 birds each and (T2) modern rearing (closed drinkers, population density of 13.8 birds/m2 and infrared gas brooders as heating source) with 10 repetitions of 6 birds each. The birds were lodged in an experimental house with semi controlled environment and reared according to the breed manual. Production variables that were measured weekly were: feed consumption, body weight, feed conversion and mortality; and finally carcass yield and pigmentation. Wellbeing variables that were measured were lesions in their footpad, hock, breast and walking gait; likewise, serum corticosterone levels were measured and adrenal tissue subjected to microscopic inspection. Results showed a favorable significant difference for T2 in feed consumption, body weight, pigmentation, carcass yield and corticosterone levels; but footpad lesions were found and these were statistically different. Histological changes were observed in adrenal glands. The results suggest that the modern rearing systems enhance better productivity; nevertheless, high population densities may be unfavorable for animal wellbeing.